Performance Analysis of VXLAN and NVGRE Tunneling Protocol on Virtual Network - Mirdan Syahid Mulya Sudrajat; Doan Perdana; Ridha Muldina Negara (Institute of Advanced Engineering and Science, 2017)
Virtualization is a new revolutionary approach in networking industry, its make possible to build several virtual machine (VM) in one physical hardware. In virtualization practice, one VM might be connected to others, but not all of VM in one environment must be connected due the privacy and security issues. One of the solutions which can address this issue is tunneling protocol. Tunneling protocol is a layer-2-in-layer-3 protocol which can isolate tenant traffic in virtualize environment. This research conducted about the performance of VXLAN and NVGRE tunneling protocol which works on virtualize environment and aims to determine the perfomances of throughput, delay, jitter, and vCPU Usage using variable packet size in range of 128-1514 byte. From the the result, can be conclude that both of tunneling protocol can isolate the traffic between tenant. For the performance result, NVGRE has the highest value of throughput, 771,02 Mbps and the VXLAN got 753,62 Mbps. For the delay NVGRE got 2.24 ms and VXLAN got 2.29 ms. For the jitter, NVGRE has better rate value of 0.361 ms, than VXLAN value of 0.348 ms, and the vCPU usage performance, NVGRE has the highest performance too that value is 60.57%. So on overall performance NVGRE has the better performance than VXLAN.